Development of lie detector using photoplethysmogram signal - Shariff, Nur Amirah; Sidek, Khairul Azami; A. Zainudin, Nur Najihah; Abdul Malik, Noreha (Malaysia Technical Scientist Association, 2019)
This study investigates the feasibility of a lie detector based on Photoplethysmograph (PPG) signal. Lie detector records physiological change of a subject under Guilty Knowledge Test (GKT). This study involved 6 subjects of age range between 23 and 24 years. Real time PPG signals were captured from a sensor that is capable of measuring the blood pressure and oxygen saturation with the help of Arduino microcontroller. The outcomes were obtained during interview session after sub-jects undergo mock crime scenario. Detailed analysis of PPG data and classification techniques shows lower results of standard deviation, peaks difference and Cardiod area calculations correspond to lie conditions. The experimental results demonstrate that PPG signal have great potential to be used as a lie detector by providing high classification performance.